Analysis of Transparency Index Measurement of Amil Zakat Institutions in Indonesia - Mutaqin, Mu'min; Yandri, Pitri (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
Abstract This study aims to measure the transparency index of zakat institutions in Indonesia. This study also shows the transparency index of OPZ (Organisation of Zakat Management) with the ZIS collection, which goes hand in hand. The analysis is conducted on 5 OPZs that are included in the category of national-level zakat institutions by digging up information on official websites and financial reports for 2019-2021. Quantitative descriptive research method using ITRANS OPZ through approximate calculation or simple additive weight (SAW) as a measuring tool. The results of this study also show the transparency index accompanied by the zakat collection for the last 3 years. The aim is to show the high OPZ transparency index and the increasing collection from year to year. OPZ can determine how much transparency has been provided and maintain, improve, and expand transparency openness. This is the basis for improving the institution's reputation to the public. OPZ can use information technology and online platforms to improve transparency. Transparent financial reports and online accessibility can facilitate muzakki access and increase trust. Keywords: Transparency, Transparency Index, Fund Raised by Zakat Institutions.   Abstrak Studi ini bertujuan untuk mengukur indeks transparansi lembaga zakat di Indonesia. Penelitian ini juga memperlihatkan indeks transparansi OPZ (Organisasi Pengelola Zakat) dengan pengumpulan ZIS yang beriringan. Analisis dilakukan terhadap 5 OPZ yang masuk dalam kategori lembaga zakat tingkat nasional dengan menggali informasi pada website resmi dan laporan keuangan tahun 2019-2021. Metode penelitian deskriptif kuantitatif dengan menggunakan ITRANS OPZ melalui perhitungan perkiraan atau simple additive Weight (SAW) sebagai alat ukur. Hasil penelitian ini juga memperlihatkan indeks transparansi yang diiringi dengan perhimpunan zakat selama 3 tahun terahir, tujuannya untuk memperlihatkan indeks transparansi OPZ yang tinggi beriringan dengan perhimpunan yang meningkat dari tahun ke tahun. OPZ dapat pengetahui seberapa besar tingkat transparansi yang sudah diberikan, menjaga, meningkatkan dan memperluas keterbukaan transparansi, hal ini sebagai dasar peningkatan reputasi lembaga kepada publik. OPZ dapat menggunakan teknologi informasi dan platform online untuk meningkatkan transparansi. Penyediaan laporan keuangan secara terbuka dan aksesibilitas online dapat mempermudah akses muzaki dan meningkatkan kepercayaan. Kata Kunci: Transparansi, Indeks Transparansi, Dana yang Dihimpun oleh Lembaga Zakat.